Large increase in global storm runoff extremes driven by climate and anthropogenic changes - Jiabo Yin (Nature Portfolio, 2018)
Storm runoff extremes dominate flash flood formation and generation, posing a grand threat to ecosystems and communities across the world. Here the authors show that current projected response of these storm runoff extremes to climate and anthropogenic changes are underestimated.